A Cost Effective Method for Determining the Position of Mine Haul Road Defects from the Road Edge - Sokolic, Frank; Rawlins, Mark; Duffy, Kevin Jan (International Journal of Interactive Mobile Technologies (iJIM), 2009)
This paper describes a simple method for estimating haul road defect positions from alongside roads. It is a method that is cheap and easy to implement, needing only a minimal amount of field equipment and training. Observers are required to estimate the bearing and distance to a defect, and to record their location using a GPS receiver. All further processing is automated and can be done entirely within a spatially-enabled database management system such as Microsoft SQL Server or PostgreSQL.